(3eNJUQ GdeSfO GdUMjMs - (3YHO GdYXje Hf YHO Gdbhj Hf YHO Gddg, CHh eMeO, Rcj GdOjf GdefPQj ,J (B656 (3g` s; (3GdGeGe eSde , CHh GdMSjf,J (B261 (3g` s ((3GdbGgQI s)
(3ChdgG (B:s
(3GdMeO ddg GdQMje GdZaGQ hHYO , agPG cJGH ENJUQJg ef UMjM GdEeGe CHj GdMSjf eSde ENJUGQkG jSgdg Ydi MGaXjg hjbQHg ddfGXQ ajg , hQJHJg JQJjHkG jSQY HGdWGdH Edi hLhO eWdHg s
(3BNQgG (B:s
(3bGd gGQhf (B: (3gd JOQi BNQ ShQI ef GdbQBf fRdJ LejYkG ? bdJ (B: (3fYe EPG LGA fUQ Gddg hGdaJM bGd (B: (3UObJ CfLR HMeO Gddg hefg hcQeg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3cJHJ GdeLehYI HQSe NRGfI GdebQ GdCTQai GdYGdi Gdehdhi GdCejQi GdSjais
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQI GdYfhGf (B:s
(3GNJUGQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdMOjK h GdeUWdMs